A facile synthesis for hierarchical porous CeO2 nanobundles and their superior catalytic performance for CO oxidation. Issue 2 (24th November 2014) - Rao, Richuan; Yang, Ming; Li, Changshun; Dong, Huaze; Fang, Song; Zhang, Aimin
Abstract : Porous CeO2 nanobundles with hierarchical nanoarchitecture show much better catalytic activities for CO oxidation compared to CeO2 nanorods, nanowires and nanoparticles. Abstract : In this study, we develop a facile hydrothermal route to build a nanostructure of porous CeO2 nanobundles with hierarchical architectures by the design and growth of anisotropic CeO2 precursors in a carbonate-assisted formaldehyde hydrothermal system without templates and surfactants. The key to this synthesis is to control the formation of their anisotropic CeO2 precursors with formate and carbonate promoted by carbonate and ammonium ions during the hydrothermal treatment. The as-prepared CeO2 nanobundles have a hierarchical porous structure assembled by numerous nanorods with a small diameter, and they show much higher catalytic activities for CO oxidation compared with CeO2 nanorods, nanowires and nanoparticles prepared by formaldehyde-assisted hydrothermal treatment and traditional precipitation methods. The outstanding catalytic performance for the nanobundles is attributed to their excellent physicochemical properties such as larger lattice cell parameters, much larger surface areas and the best redox behaviour of surface oxygen on the CeO2 surface.